2009
DOI: 10.1666/0094-8373-35.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Relative taxonomic and ecologic stability in Devonian marine faunas of New York State: a test of coordinated stasis

Abstract: The concept of coordinated stasis, manifest as a pattern of long intervals of concurrent taxonomic and ecologic persistence separated by comparatively abrupt periods of biotic change, has been challenged in recent studies that claim a lack of prolonged persistence of taxa and associations. A key problem has been the difficulty of distinguishing faunal change owing to localized, short-term environmental fluctuation or patchiness from that indicating regionally pervasive, long-term evolutionary or ecological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 65 publications
(68 reference statements)
1
47
0
Order By: Relevance
“…This kind of compositional persistence, or recurrence also has been documented in terrestrial wetland vegetation from Carboniferous lowland environments (e.g., DiMichele et al, 2002), and for normal marine benthic faunas from Mississippian environments (e.g., Bonelli and Patzkowski, 2011). These kinds of patterns in both terrestrial and marine environments have been attributed to relatively narrow ranges of physical environmental tolerance by most organisms, resulting in strong patterns of habitat tracking through space and time (e.g., Brett et al, 2007;DiMichele et al, 2008), and, as observed by Ivany et al (2009), may account for observed larger spatio-temporal scale, evolutionary-ecological patterns.…”
Section: Discussionmentioning
confidence: 81%
“…This kind of compositional persistence, or recurrence also has been documented in terrestrial wetland vegetation from Carboniferous lowland environments (e.g., DiMichele et al, 2002), and for normal marine benthic faunas from Mississippian environments (e.g., Bonelli and Patzkowski, 2011). These kinds of patterns in both terrestrial and marine environments have been attributed to relatively narrow ranges of physical environmental tolerance by most organisms, resulting in strong patterns of habitat tracking through space and time (e.g., Brett et al, 2007;DiMichele et al, 2008), and, as observed by Ivany et al (2009), may account for observed larger spatio-temporal scale, evolutionary-ecological patterns.…”
Section: Discussionmentioning
confidence: 81%
“…Of course, time to recovery is not related to difficulty of transition, so the time course of a transition has no bearing on hysteresis or alternative community states. The biotic stability of coral reefs on centennial, millennial, and longer time scales is most parsimoniously viewed as an indication of the stability of environmental drivers (Aronson et al 2002a(Aronson et al , 2002b(Aronson et al , 2005, in the absence of evidence to the contrary (Ivany et al 2009). …”
Section: Discovery Bay Jamaicamentioning
confidence: 99%
“…Thus, these three species likely played a major role in the structure of the food web and interspecies relationships. Because of the large timespan of the Escuminac Formation, a coordinate and evolutionary stasis (Brett et al 1996, Ivany et al 2009 has been suggested for the Escuminac assemblage (Cloutier et al 2011). A long duration stasis is only possible if links between species are strong and explained by ecological stability and complexity as suggested by biostratigraphic distribution of taxa and the trophic structure of the Escuminac assemblage.…”
Section: Generalized Devonian Estuarine Conditionsmentioning
confidence: 99%